(3GdeYGdLI GdbGfhfjI hGdbVGFjI dLQGFe GdeNOQGJ aj eUQ hOhd GdNdjL GdYQHjI (B:s (3EMQGR Ohf bUO(B-(3JYGWj(B-(3EJLGQ(B-(3LdH (B/s - (3HOQ, CMeO SdGeIs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3GdeYGdLI GdbGfhfjI hGdbVGFjI dLQGFe GdeNOQGJ aj eUQ hOhd GdNdjL GdYQHjI(B) (3hGdPj bGe HJCdjag (B((3CMeO SdGeI HOQ(B) (3aj MhGdj (B(294) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bhGfjf LQGFe GdeNOQGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3LQjeI EMQGR GdeNOQ HOhf bUO aj eUQ, hjTed GdeHMK GdChd (B: (3LQjeI EMQGR GdeNOQGJ HOhf bUO aj eUQ, GdeHMK GdKGfj (B: (3LQjeI EMQGR GdeNOQGJ HOhf bUO aj Ohd GdNdjL(B... (3EdN(B.s
(3ebQQGJ OQGSjI (B2025-2026.s
Keywords: (3GdeNOQGJs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdeNOQGJs -- (3bhGfjf hJTQjYGJs -- (3Ohd GdNdjL GdYQHjIs